PRODUKTIVITAS DAN BIAYA PENYARADAN KAYU DENGAN TRAKTOR PERTANIAN TYPE FORD 5660 DI HUTAN TANAMAN SEMARAS, PULAU LAUT - Dulsalam Dulsalam; Sukadaryati Sukadaryati (Pusat Penelitian dan Pengembangan Hasil Hutan, 2002)
Investigation on assessing the productivity and cost of log-skidding using a farm tractor type Ford 5660 was carried out at the Semaras plantation forest under PT. lnhutani's concession situated in Pulau Laut (South Kalimantan) in 1999. The objective was to get appropriate and reliable information on the productivity and cost of log-skidding. The data collected were skidding-distance, working time, log volumes, purchasing- cost. and labor wage; and further, they were all incorporated for assessment.The results were: I). Log volumes skidded using the farm tractor ranged between 0.065 - 1.134 m3/ one- trip with an average of 0.434 m3/one- trip, while skidding-distance varied from 0.25 - 1.85 hm with an average of 0.937 hm, 2). Skidding time was in the range of 0.06 - 1. 14 hours/one-trip with an average of 0.23 hours/one-trip, 3). The productivity of log-skidding using the farm tractor recorded between 0.062 -6.086 m3-hm/hour with an average of 2.075 m3-hm/hour, while the cost of log-skidding was in the range of Rp 9,522/m3-hm - Rp 931,000/m3-hm with average at Rp 55.777/m3-hm. and 4). In implemanting the use of fram tractor for logskidding, the log volume and skidding-distance are suggested at about 1.2 m3 and 2 hm, respectively.